Use of Thyroid Hormones in Hypothyroid and Euthyroid Patients; the 2019 Italian Survey. Issue 1 (4th January 2020) - Negro, Roberto; Attanasio, Roberto; Nagy, Endre V.; Papini, Enrico; Perros, Petros; Hegedüs, Laszlo
Abstract : Background: The incidence and prevalence of hypothyroidism are increasing and the threshold for the treatment of hypothyroid as well as individuals without evident thyroid disease with thyroid hormone is declining. Objective: To investigate endocrinologists' use of thyroid hormones in hypothyroid and euthyroid patients in Italy, a country where different formulations of levothyroxine (LT4; tablet, liquid solution and soft-gel capsule) are available on the market. Methods: Members of the Associazione Medici Endocrinologi (Italian Association of Clinical Endocrinologists) were invited to participate in a web-based survey investigating the topic. Results: A total of 797 of 2, 028 (39.3%) members completed all the sections of the survey; 98.7% declared that the treatment of choice for hypothyroidism is LT4. A significant minority (37.3%) indicated that LT4 may be considered in infertile euthyroid women seeking pregnancy and harbouring positive thyroperoxidase antibodies (TPOAb) and in goitre increasing in size (18.1%). LT4 + LT3 was considered by 43.2% for LT4-replaced patients and normal TSH, if they reported persistent symptoms. High percentages of respondents chose LT4 in a liquid solution or soft-gel capsules when taken together with other drugs interfering with LT4 absorption (81.8%), in patients with a history of celiac disease, malabsorption, lactose intolerance, intolerance to common excipients (96.6%), or unexplained poor biochemical control of hypothyroidism (74.4%), or in patients not able to adhere to ingesting LT4 fasted and/or separated from food/drink (98.9%). In total, 43.6% of responders would use LT4 in a liquid solution or soft-gel capsules for hypothyroid patients with biochemical euthyroidism on LT4, who had persistent symptoms. Conclusions: The preferred treatment for hypothyroidism is LT4; LT3 + LT4 combination treatment is mainly considered in patients with persistent symptoms. A significant minority would offer LT4 to euthyroid women with positive TPOAb and infertility and to euthyroid patients with progressive simple goitre. Alternative LT4 formulations like liquid solution or soft-gel capsules are largely reserved for specific conditions (interfering drugs, actual or suspected malabsorption, inability to take LT4 in the fasting state, unexplained poor biochemical control of hypothyroidism).